Immunocytochemistry and DNA-image Cytometry in Diagnostic Effusion Cytology. II. Diagnostic Accuracy in Equivocal Smears - Helma Motherby; Nicolaus Friedrichs; Mary Kube; Bahram Nadjari; Kristiane Knops; Andreas Donner; Betty Baschiera; Peter Dalquen; Alfred Böcking (Analytical Cellular Pathology)
To determine sensitivity and specificity of different antibodies for the immunocytochemical detection of malignant cells in diagnostically equivocal effusions in comparison with those achieved by DNA‐image cytometry. 65 cytologically doubtful effusions of the serous cavities were stained with twelve antibodies. Furthermore, DNA‐image cytometry was performed. Data were correlated with patient follow‐up. Sensitivity of cellular staining of Ber‐EP4 for the identification of malignant cells was 77.8%, specificity of absent staining for benign cells was 100%. Positive predictive value for the identification of malignant cells was 100%, negative value 65.5%. Sensitivity of DNA‐aneuploidy for the identification of malignancy was 82.9%, specificity of DNA‐non‐aneuploidy for benignity 94.7%. The positive predictive value of DNA‐aneuploidy for the occurrence of malignant cells was 96.7%. Negative predictive value of DNA‐non‐aneuploidy was 72.0%. Combining immunocytochemistry applying Ber‐EP4 only and DNA‐cytometry in equivocal effusions resulted in a sensitivity of 88.9% for the identification of malignant cells associated with a 95.0% specificity. Positive predictive value was 97.7%, the negative one 79.2%.